Antimicrobial resistance in clinical Escherichia coli isolates obtained from animals - M. N. Isakova; O. V. Sokolova; N. A. Bezborodova; A. S. Krivonogova; A. G. Isaeva; V. D. Zubareva (Ветеринария сегодня)
The article presents data on the phenotypic and genotypic characteristics of antimicriobial resistance in Escherichia coli clinical isolates recovered from bovine microbiota (secretions from mammary glands, cervical swabs). 127 Escherichia coli isolates were studied, i.e. 44 from mammary glands secretions and 83 from cervical swabs. Disk diffusion method was used to study antimicrobial resistance of the cultures; minimum inhibitory concentrations of antimicrobials were determined in a serial dilution method; resistance genes were detected by polymerase chain reaction. The carried out research demonstrates a wide distribution of the isolates belonging to the phenotype resistant to ansamycins (rifampicin), semi-synthetic penicillins (ampicillin and amoxicillin), tetracyclines (doxycycline). The isolates showed a lower level of resistance to macrolides (azithromycin), amphenicols (levomycetin) and aminoglycosides (tobramycin). It was found that Escherichia coli clinical isolates are sensitive to third-generation cephalosporins and fluoroquinolone antimicrobials. However, since 28.46% of cultures demonstrate intermediate resistance to third-generation cephalosporins and 49.02% of Escherichia coli DNA samples isolated from mammal gland secretions had blaDHA gene associated with resistance to this group of antimicrobials, these antimicrobials could be hardly recommended as antibiotics of choice. Absence of VIM carbapenemase-encoding gene in the DNA of the recovered isolates and a low level of phenotypic resistance (10.22% of isolates from cervical swabs) can be one of the reasons for recommending first-line carbapenems as antibiotics of choice to treat animal diseases associated with Escherichia coli, along with fluoroquinolones as reserve antimicrobials. It was found that the recovered Escherichia coli isolates are more sensitive to combination antibiotics than to mono-antibiotics.